A questionnaire-based investigation of the swimming puppy syndrome: 115 dogs - Rumpel, Lea; Kölle, Petra; Mille, Monika A.; Lauer, Susanne K.; Zablotski, Yury; Fischer, Andrea (Frontiers in Veterinary Science, 2023)
Swimming Puppy Syndrome (SPS) is a benign reversible condition of unknown etiology in multiple dog breeds. Affected dogs show laterally abducted limbs and are unable to stand and walk on their own. The current knowledge of this condition derives from few case reports or small case series. Therefore, the aim of this study was to collect data on the clinical course from a large cohort of dogs with SPS with an online questionnaire supported by video footage. Potential risk factors were compared between 110 litters with SPS and 103 unaffected litters. SPS was reported in 115 dogs from 48 different breeds comprising a wide range of small, middle, and large breeds. Litters with SPS were significantly smaller than unaffected litters. Cesarean sections were reported more frequently in affected litters, but the overall rate of reported birth complications did not differ significantly from unaffected litters. Most puppies were able to stand and walk at a median age of 4.5 weeks (up to 12 weeks) and clinical signs resolved at a median age of six weeks (up to 12 weeks). Puppies from large breeds showed faster recovery than puppies from medium and small breeds. Occasionally, residual deficits were reported and only three dogs failed to recover. A clustering of SPS occurred in closely related litters in four kennels of four different dog breeds (Greater Swiss Mountain Dog, Golden Retriever, Miniature Bull Terrier, Norwich Terrier). The study shows the benign clinical course of SPS in a large cohort of puppies from multiple dog breeds. Potential risk factors including reports on birth complications, size and muscle mass compared to littermates and diet of the dam during pregnany were evaluated and no influence on the occurrence of SPS was identified.